Residual dizziness after BPPV management: exploring pathophysiology and treatment beyond canalith repositioning maneuvers - Özgirgin, O. Nuri; Kingma, Herman; Manzari, Leonardo; Lacour, Michel (Frontiers in Neurology, 2024)
Despite the high success rate of canalith repositioning maneuvers (CRMs) in the treatment of benign paroxysmal positional vertigo (BPPV), a growing number of patients report residual dizziness symptoms that may last for a significant time. Although the majority of BPPV cases can be explained by canalolithiasis, the etiology is complex. Consideration of the individual patient’s history and underlying pathophysiology of BPPV may offer the potential for treatment approaches supplementary to CRMs, as well as a promising alternative for patients in whom CRMs are contraindicated. This article provides a summary of the possible underlying causes of BPPV and residual dizziness, along with suggestions for potential management options that may be considered to relieve the burden of residual symptoms.